Bantuan Hukum dan Pembelaan Hak-Hak Masyarakat (Sejarah dan Perkembangannya): Bantuan Hukum dan Pembelaan Hak-Hak Masyarakat (Sejarah dan Perkembangannya) - Zulherman Idris; Miftahur Rachman; Wira Atma Hajri; Erlina (UIR Law Review, 2022)
The topic of Legal Aid Institutions is an important topic to discuss, because all of this is closely related to law enforcement and the expected goals of the law. This means that in the existing legal phenomenon, it turns out that law enforcement often results in injustice, so it is like an anecdote which states that “law enforcement is blunt upwards and sharp downwards". In fact, we often hear that law enforcement is always related to “will and power”, especially when it comes into contact with small and poor groups.